Hermeneutics of Doctrine in a Learning Church : The Dynamics of Receptive Integrity - Ryan, Gregory A., (Studies in Systematic Theology ;, 2020)
In Hermeneutics of Doctrine in a Learning Church , Gregory A. Ryan offers an account of the dynamic, multi-dimensional task of interpreting Christian tradition. He integrates doctrinal hermeneutics, the 'pastorality of doctrine' exemplified by Pope Francis, and a systematic appraisal of Receptive Ecumenism to provide an original perspective on this task. The book focuses on three contemporary Catholic theologians (Francis Schüssler Fiorenza, Ormond Rush, and Paul D. Murray), highlighting how each recognises the dynamic interaction of multiple perspectives involved in authentic ecclesial interpretation. Christian tradition, whether passed on in teaching, scripture, practices, or structures, needs to be continually received and interpreted. This book offers theologians, ecumenists, and church workers a fresh model for receptive ecclesial learning in which doctrinal hermeneutics and pastoral realities are dynamically integrated.